(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Several studies have demonstrated that Wilms’ tumour gene 1 (WT1) is consistently overexpressed in most forms of leukemias, and the usefulness of quantitative assessment of WT1 expression as a molecular marker for minimal residual disease (MRD). Many suggest a role of WT1 for angiogenesis in hematological malignancies, WT1 is also expressed in a large variety of tumour blood vessels, and some suggests that it might be a general marker for angiogenesis. Objective:To assess the role of WT1 protein expression immunohistochemically in chronic myeloid leukemia (CML) and to determine whether there is a correlation between WT1 protein expression and CD31 expression as a marker of angiogenesis. Methods:This study involved 16 cases of newly diagnosed CML. In addition, 20 age matched control cases were involved having no apparent bone marrow pathology. Immunohistochemistry was done on bone marrow biopsies using Anti-WT1 and Anti-CD31 Monoclonal antibodies. Results:There was a significant increase in WT1 protein expression in CML cases, as well as an increase in CD31 expression; however, there was no significant correlation between WT1 expression and hematological parameters (WBC count, platelets count, PCV level, and peripheral blood blast %) and CD31 expression. Conclusion:This study showed that WT1 is overexpressed in CML patients, while it was undetected in controls, thus we may propose that it maybe used as an auxiliary marker for the disease. WT1 expression was not found to be of prognostic significance. Moreover CD31 as a marker for angiogenesis was significantly increased in CML but did not correlate with WT1 expression. Key words: WT1, chronic myeloid leukemia, immunohistochemistry